Cultura e socialização de bolivianos em duas escolas públicas estaduais na cidade de São Paulo - Miyahira, Elbio (2022)
The objective of this research is to analyze the socialization and the construction of the cultural identity of Bolivian immigrant students within their school relations. Two public schools in the central region of São Paulo were the focus of this research. The adopted instrument research was the sociometric test, the observation in the classroom, and the Likert scale to analyze the context in which foreign students and children of foreigners are inserted and how they work their cultural identity and socialization in this school context. The theoretical framework used was the concepts of Stuart Hall (2003, 2014, 2015) and Woodward (2014), that, when studying immigration, consider culture to be dynamic, in constant production of oneself. They understand the identity as something built through differentiation and they report the existence of an ideological basis in societies. This basis always tries to build a hegemony in the communication of values. We also used the concepts of Bauman (2003, 2005, 2012, 2013), considering identity as negotiable by the individual based on the possessed elements. On the one hand, identity can defend the individual from the smaller group to which s/he is inserted, and, on the other hand, it can be used to defend this smaller group from the larger groups, in the latter case, the smaller group requires strong loyalty from the individual. The hypotheses of this research are: 1. Schools tend to create hegemonic communication through their pedagogical practices. Behind the discourse of equal treatment, there is a tendency to devalue immigrants’ identity and culture. 2. Despite the restricted socialization of Bolivians with Brazilian students, there is a reconstruction of their cultural identity by the immigrant. They are constantly producing identity through differentiation. 3. Bolivian students in public schools tend not to socialize a lot with Brazilian students in the classroom and do not establish any relationship outside it